Culture Specific Item Analysis in Determining the Translator Ideology in the The Necklace Short Story - Firda Zuldi Imamah; Agus Subiyanto (Universitas Nahdlatul Ulama Blitar, 2020)
Translator has a choice in translating text which contains cultural and social background of source language. It determines the translators ideology toward their stance in introducing or maintaining the culture language. The ideology of translator can be seen through one of the ways which is they translating the CSI of source text. The translation techniques is used to examine the CSI could identify the ideology they choose. This research aims to examine the translator ideology through CSI analysis in the translation text from English to Indonesian of short story The Necklace. This research used descriptive qualitative method. The result shows that the translator tends to choose domestication ideology since the setting, theme and plot of the story makes the target reader feels relatable experience while reading it. Therefore, translator used translation techniques which contributed to maintenance the readability, equivalency, and acceptability of the source text.